The Effect of Communication Skill and Transformational Leadership on Employee Performance with Knowledge Sharing as an Intervening Variable (Case Study: Matahari Department Store Java Supermall Semarang) - Putri Yani; Yulekhah Ariyanti; Ratih Pratiwi; Jati Kusuma (International Journal of Management and Business Economics, 2022)
This study aims to determine and analyze the effect of communication skills and transformational leadership on employee performance with knowledge sharing as an intervening variable. This type of research used in this research is quantitative research. The sample in this study were 75 employees of the Matahari Department Store Java Supermall. Processing and data analysis using SPSS version 21 for Windows. The results showed that communication skills have a significant positive effect on knowledge sharing, transformational leadership has a significant positive effect on knowledge sharing, communication skills have a positive and insignificant effect on employee performance, transformational leadership has a significant positive effect on employee performance, knowledge sharing has a significant positive effect on employee performance, Communication skills do not have an indirect effect on employee performance with knowledge sharing as an intervening variable, and transformational leadership has an indirect effect on employee performance with knowledge sharing as an intervening variable. The results of this study are discussed based on previous evidence, and the implications can be used for organizations or companies engaged in the same or other fields.